Effect of Dy substitution on the microstructure and magnetic properties of high (BH)max Nd-Dy-Fe-Co-B nanoparticles prepared by microwave processing - Tan, Xiao (2021)
Nd-Fe-B based magnets possess the largest energy product and are essential in numerous cutting-edge applications. We report the bottom up, energy efficient, cost effective microwave synthesis of Dy alloyed Nd2(Fe,Co)14B magnetic nanoparticles. The process included microwave combustion to synthesize Nd-Dy-Fe-Co-B mixed oxides, followed by the reduction of these oxides by CaH2. The influence of Dy substitution on both room temperature and temperature dependent magnetic properties were investigated. For (Nd12Dy3)-(Fe67Co10)-B8 alloy, (BH)max was found to be as high as 12.6 MGOe. The coercivity increased significantly, from 8 kOe to 14.5 kOe, as Dy content increased from x = 0 to x = 9. The thermal coefficient of remanence (α) and thermal coefficient of coercivity (β) were also determined, it was found that thermal stability increased for higher Dy content. Analysis of temperature dependent magnetic properties and comparison with modeling results showed that the dominant coercivity reversal mechanism of these particles was nucleation of reversed magnetic domains.